Improved synthetic spectra of helium-core white dwarf stars - Rohrmann, Rene Daniel (2002)
We examine the emergent fluxes from helium-core white dwarfs following their evolution from the end of pre-white dwarf stages down to advanced cooling stages. For this purpose, we include a detailed treatment of the physics of the atmosphere, particularly an improved representation of the state of the gas by taking into account non-ideal effects according to the so-called occupation probability formalism. The present calculations also incorporate hydrogen-line opacity from Lyman, Balmer and Paschen series, pseudo-continuum absorptions and new updated induced-dipole absorption from H2-H2, H2-He and H-He pairs. We find that the non-ideal effects and line absorption alter the appearance of the stellar spectrum and have a significant influence upon the photometric colours in the UBVRI-JHKL system. This occurs specially for hot models Teff ≳ 8000 owing to line and pseudo-continuum opacities, and for cool models Teff ≲ 4000 where the perturbation of atoms and molecules by neighbouring particles affects the chemical equilibrium of the gas. In the present study, we also include new cooling sequences for helium-core white dwarfs of very low mass (0.160 and 0.148 M⊙) with metallicity Z = 0.02. These computations provide theoretical support to search for and identify white dwarfs of very low mass, specially useful for recent and future observational studies of globular clusters, where these objects have began to be detected.